Trends in Publication and Levels of Evidence in Foot and Ankle International From 2000-2015. Issue 3 (14th September 2018) - Griffith, Matthew; Han, Edward; Hattaway, Joshua; Huh, Jeannie
Category: Other Introduction/Purpose: As the movement towards evidence-based medicine grows and publication rates rise each year, critical analysis of the orthopaedic literature has become increasingly important. To aid readers in assessing the scientific quality of published research, Foot and Ankle International (FAI) began assigning levels of evidence to all clinical articles in 2008. The purpose of this study was to analyze trends in the characteristics and levels of evidence of articles published in FAI between 2000 and 2015. Methods: All articles published in FAI from 2000, 2005, 2010, and 2015 were reviewed and categorized into article type (clinical, basic science, review, or technical tip). Each clinical article was assigned a level of evidence (I-V) and study type (prognostic, therapeutic, economic, or diagnostic). Descriptive information was gathered pertaining to: country of origin, authorship, and funding. Statistical analysis was performed using chi-squared tests to detect any trends in levels of evidence and publication characteristics. Results: 647 articles were reviewed from 2000 to 2015. There was a statistically significant increase in the publication of clinical articles (70% to 83%; p=0.013). The publication of levels I and II evidence significantly increased (2.44% to 13.53%; p=0.002). Although levels III-V evidence also increased (65% to 70.6%, p=1.014), this was not statistically significant. Publications originated from 39 countries, with a significant increase in the proportion of international papers (32.8% to 48%%; p=0.007). The proportion of articles authored by Podiatrists during the study period significantly decreased (3.73% to 1.74%, p=0.035). Finally, there was an increase in funding disclosures during the study period; funding from grants or professional groups rose from 2.44% to 15.9% (p<0.001) and reported funding from commercial sources rose from 0% to 9.41% (p=0.002). Conclusion: The proportion of level I and II studies published in FAI significantly increased from 2000 to 2015. The publication of clinical research rose, with a majority being therapeutic studies. There was a significant increase in articles published by international authors and a significant decrease in articles published by DPMs. During the same time period, there was a rise in the proportion of articles reporting the use of outside funding, both professional and commercial.